2020
DOI: 10.1021/acs.orglett.9b04269
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tribenzo[b,d,f]azepines via Cascade π-Extended Decarboxylative Annulation Involving Cyclic Diaryliodonium Salts

Abstract: Various functionalized tribenzo­[b,d,f]­azepines were prepared efficiently with the readily available 2-aminobenzoic acids and cyclic hypervalent diaryliodonium reagents as starting materials under Pd­(II) catalysis. The key of this step-economical protocol is that the carboxylic acid functionality was employed as both a traceless directing group for the N–H activation/arylation and a functional handle for the tandem π-extended decarboxylative annulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Even if tandem reactions including various sequences combining oxidation reactions or nucleophilic additions are widespread [130], tandem catalytic couplings on heteroarenes are really sparse and still remain a great challenge. Although decarboxylative cross-coupling reactions are not covered in this review, it is worth mentioning two recent reports from the group of Zhang who reported the tandem π-extended decarboxylative annulation [131,132]. Significant achievements have been reported by Greaney in the last 5 years, who was the first to describe tandem N-/N-, C-/N-and N-/C-arylation starting from unprotected heteroarenes and acyclic diaryliodoniums [133].…”
Section: Atom-economical Tandem N-h/ch Arylation Of Heteroarenesmentioning
confidence: 99%
“…Even if tandem reactions including various sequences combining oxidation reactions or nucleophilic additions are widespread [130], tandem catalytic couplings on heteroarenes are really sparse and still remain a great challenge. Although decarboxylative cross-coupling reactions are not covered in this review, it is worth mentioning two recent reports from the group of Zhang who reported the tandem π-extended decarboxylative annulation [131,132]. Significant achievements have been reported by Greaney in the last 5 years, who was the first to describe tandem N-/N-, C-/N-and N-/C-arylation starting from unprotected heteroarenes and acyclic diaryliodoniums [133].…”
Section: Atom-economical Tandem N-h/ch Arylation Of Heteroarenesmentioning
confidence: 99%
“…Greaney and co-workers have designed excellent reaction patterns using nitrogen-containing heterocycles including indole, pyrazole and triazole to achieve dual arylation. 6,7 Of note, these heterocycles are employed as nucleophiles for the first arylation to form C–N bonds and subsequently as C–H activation groups to complete the second arylation (Scheme 1b). 7…”
mentioning
confidence: 99%
“…Some tribenzo­[ b , d , f ]­azepine derivatives exhibit novel pharmacological properties . Furthermore, 9 H -tribenzo­[ b , d , f ]­azepines are also essential intermediates in the synthesis of the functional materials and bioactive molecules. , However, synthetic methods for tribenzo­[ b , d , f ]­azepines are rare and should be developed …”
mentioning
confidence: 99%